How and when leader narcissism links to employees’ objective career success: The roles of ingratiation and careerist orientation - Ding, Zhihui; Liu, Mingwei; Quan, Lei; Wang, Huaqiang; Zhang, Pengcheng; Liu, Wenxing (Frontiers in Psychology, 2023)
Previous researches have emphasized the value of leader narcissism on employees’ career success, whereas we still know little about how and when this relationship will materialize. By integrating dramaturgical theory and leader narcissism literatures, we propose a theoretical model to explain the mechanism and boundary of leader narcissism in promoting employees’ objective career success (e.g., salary increases and promotions). To test our hypotheses, we carried out a multi-wave research design and collected data from 299 employees in Chinese manufacturing firms. The results of multiple regression analysis showed that leader narcissism motivates employees’ ingratiation, which in turn facilitates employees’ objective career success, especially when those employees are high in careerist orientation. Theoretical and practical implications of the findings are discussed.